1985
DOI: 10.1080/00102208508960384
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Analysis of Laminar Flame Propagation with Variable Transport Coefficients

Abstract: This paper reports an extended formula for the burning velocity of a steady onedimensional, planar, adiabatic flame in the case of a one-step irreversible decomposition reaction. As a generaliiation of previous analyses, which were concerned with constant-property flames, variable transport coefficients and variable mean molecular weight are taken into account. The resulting effects on the burning velocity are discussed and explained on physical grounds. A distinguished downstream zone involving a convective-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The structure to be sought is one in which the upstream conduction occurs in a convective-diffusive zone, the main reaction occurs in a reactive-diffusive zone, and a convective-reactive zone is encountered downstream, where the temperature continues to increase but does so more slowly, the temperature always being presumed to be below 7^i n of Figure 1; (the hot flame can develop only when T > T m J. It will be found that a distinguished convective-reactive-diffusive transition region is needed between the main reaction zone of the cool flame and the convective-reactive region; distinguished zones of this type have been encountered in previous flame-structure analyses, for example in applications of activation-energy asymptotics to ordinary flames with reaction orders greater than unity (Rogg and Williams, 1985).…”
Section: Cool Flamesmentioning
confidence: 99%
“…The structure to be sought is one in which the upstream conduction occurs in a convective-diffusive zone, the main reaction occurs in a reactive-diffusive zone, and a convective-reactive zone is encountered downstream, where the temperature continues to increase but does so more slowly, the temperature always being presumed to be below 7^i n of Figure 1; (the hot flame can develop only when T > T m J. It will be found that a distinguished convective-reactive-diffusive transition region is needed between the main reaction zone of the cool flame and the convective-reactive region; distinguished zones of this type have been encountered in previous flame-structure analyses, for example in applications of activation-energy asymptotics to ordinary flames with reaction orders greater than unity (Rogg and Williams, 1985).…”
Section: Cool Flamesmentioning
confidence: 99%